Development of Innovative Dietary Supplements from DHA And Probiotics - Pattarabovornwut, Kasipat; Watthanabut, Busakorn; Chaikhumwang, Puwich (Journal of Ecohumanism, 2024)
This research investigated the development of innovative dietary supplements combining Docosahexaenoic Acid (DHA) and probiotics. The increasing prevalence of lifestyle-related diseases has driven interest in supplements offering multiple health benefits. DHA, an omega-3 fatty acid, is known for its cognitive, cardiovascular, and anti-inflammatory properties, while probiotics support gut health and immune function. Combining these components presents a promising approach to health management due to their synergistic effects. However, challenges exist in commercializing such supplements, including varying regulatory frameworks, ensuring probiotic stability and safety, and overcoming consumer resistance to the fishy odor associated with DHA. The study employed a multi-phased methodology, using qualitative and quantitative research methods (focus groups, in-depth interviews) to guide product development. This iterative process led to "Geni Pro," a jelly-based supplement with three fruit flavors (orange, strawberry, and blueberry), designed to be palatable and convenient, especially for children. The commercialization strategy considered consumer preferences, using pharmacies and online platforms as primary sales channels. Regulatory compliance was ensured through FDA registration in Thailand. This research contributes to the body of knowledge by offering a comprehensive approach to developing and commercializing innovative dietary supplements, mainly focusing on consumer preferences and addressing the challenges in this area. Further research could explore the synergistic effects of DHA and probiotics at a molecular level and investigate long-term benefits in specific health conditions.